الحوكمة في الصفقات العمومية كآلية للوقاية من الفساد في التشريع الجزائري - كالي ،حليمة (جامعة الوادي University of El Oued, 2024)
تمثل الصفقة العمومية الأسلوب الأمثل الذي تستخدمه الدولة لتلبية حاجيات مواطنيها والنهوض بالدولة نحو تنمية مستدامة في جميع المجالات وبالمقابل فهي تعتبر أو بالأحرى تمثل الأرضية الخصبة لانتشار ظاهرة الفساد، وكون الفساد ظاهرة مركبة متعددة الجوانب فإن إعمال مبادئ الحوكمة وتكريسيها في التشريعات التي تنظم الصفقات العمومية أضحى ضرورة ملحة لذلك وهو ما أخذ به المشرع الجزائري منذ سنة 2010 كآلية وهذا من أجل الوقاية من الفساد في مجال الصفقات العمومية، فاعتمد على مبادئ مهمة وأساسية كمبدأ الشفافية ومبدأ المساواة ومبدأ المنافسة وذلك لتأمين مسار سليم لصفقة، واعتمد أيضا آلية تفعيل الرقابة القبلية سواء كانت داخلية أو خارجية في جميع مراحل إبرام الصفقة كآلية فعالة للحد والوقاية من الخرق للقوانين والنصوص المنظمة لها وبالتالي الحد من الفساد في مجال الصفقات العمومية والحفاظ على المال العام من التبديد عند الإنفاق العام الذي تعتبر الصفقات العمومية أكبر أبوابه. The public transaction represents the ideal method used by the state to meet the needs of its citizens and advance the state towards sustainable development in all fields. In return, it is considered, or rather represents, the fertile ground for the spread of the phenomenon of corruption. Since corruption is a complex, multi-faceted phenomenon, implementing the principles of governance and enshrining them in the legislation that regulates public transactions has become a necessity. It is urgent for this, and this is what the Algerian legislator has adopted since the year 2010 as a mechanism in order to prevent corruption in the field of public transactions. It relied on important and basic principles such as the principle of transparency, the principle of equality and the principle of competition in order to secure a sound path for a deal. It also adopted a mechanism for activating tribal oversight, whether internal or External at all stages of concluding a deal as an effective mechanism to limit and prevent violations of laws and texts regulating them, thus reducing corruption in the field of public procurement and preserving public money from wasting public spending, of which public procurement is considered the largest.
ماستر اداري